Prevalence of Lynch syndrome in a Middle Eastern population with colorectal cancer. Issue 11 (24th February 2015) - Siraj, Abdul K.; Prabhakaran, Sarita; Bavi, Prashant; Bu, Rong; Beg, Shaham; Hazmi, Mohsen Al; Al‐Rasheed, Maha; Al‐Assiri, Mohammed; Sairafi, Rami; Al‐Dayel, Fouad; Al‐Sanea, Nasser; Uddin, Shahab; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Lynch syndrome (LS; hereditary nonpolyposis colorectal cancer) is a common cause of hereditary colorectal cancer (CRC). CRC is the most common cancer diagnosed among males in Saudi Arabia but to the authors' knowledge there is a lack of data regarding the prevalence of LS in patients with CRC. There currently are no clear guidelines for the selection criteria for these patients to screen for LS. METHODS A comprehensive molecular characterization was performed in a cohort of 807 CRC cases by immunohistochemical and microsatellite analysis using polymerase chain reaction. BRAF mutation screening, high CpG island methylator phenotype, and analysis for germline mutations were performed in 425 CRC samples. These were all high microsatellite instability (MSI‐H) samples (91 cases), all low MSI samples (143 cases), and selected cases from the microsatellite stable group (191 cases) that met revised Bethesda guidelines. RESULTS Polymerase chain reaction identified 91 MSI‐H cases (11.3%) and sequencing revealed mismatch repair germline mutations in 8 CRC cases only. Of the total of 807 CRC cases, these 8 cases (0.99%) were MSI‐H, met the revised Bethesda guidelines, and did not harbor BRAF mutations. CONCLUSIONS The results of the current study confirmed cases of LS in approximately 1.0% of CRC samples and reflects the efficacy of screening among MSI‐H cases that lack BRAF mutations. This comprehensive study from Saudi Arabia will help in implementing a universal screening/reflex testing strategy in a clinical setting in Saudi Arabia and in conducting a national screening program that benefits both patients and their relatives. Cancer 2015;121:1762–1771. © 2015 American Cancer Society.